Geriatric Nutritional Risk Index and Survival of Patients With Colorectal Cancer: A Meta-Analysis - Zhao, Haiming; Xu, Li; Tang, Peng; Guo, Rui (Frontiers in Oncology, 2022)
Background: Geriatric nutritional risk index (GNRI) is an indicator of nutritional status derived by serum albumin level and ideal body weight, which has been proposed as a predictor of prognosis for elderly population with various clinical conditions. The objective of the meta-analysis was to comprehensively evaluate the association between baseline GNRI and survival of patients with colorectal cancer (CRC). Methods: Cohort studies were identified by search of PubMed, Embase, and Web of Science databases from inception to January 05, 2022 according to the aim of the meta-analysis. A random-effect model incorporating the potential between-study heterogeneity was adopted to pool the results. Results: Nine studies including 3658 patients with CRC contributed to the meta-analysis. Results showed that CRC patients with lower GNRI at baseline had worse overall survival (OS, hazard ratio [HR] 2.39, 95% confidence interval [CI] 1.78-3.23, p<0.001; I2=60%) and progression-free survival (PFS, HR 1.77, 95% CI 1.38-2.26, p<0.001; I2=33%). The results were consistent in sensitivity analyses limited to elderly patients (HR for OS 2.25, p<0.001; HR for PFS 1.65, p=0.003). Subgroup analyses showed consistent results in patents with different cancer stages, and in studies with median follow-up < and ≥ 5 years (p for subgroup effects all < 0.05). Conclusion: A lower GNRI at baseline may be independent associated with poor survival outcomes of patients with CRC. Evaluating the nutritional status using GNRI may be important for risk stratification of patients with CRC.